Competitive and complementary effects of bhindi- cowpea intercropping system in summer rice fallows - Kalarani S (Department of Agronomy, College of Agriculture, 1995)
An experiment was conducted in the summer rice fallows of the Instructional Farm attached to the college of Agriculture, Vellayani during March 1993 with the objective of assessing the possibility of raising cowpea as intercrop in bhindi and evaluating the crop association effects in different planting patterns and varying nitrogen levels. The study also aims to evaluate the biological efficiency and economic feasibility of bhindi + cowpea intercropping system. The treatments consisted of two planting patterns viz. normal row planting (G1) of bhindi at 60x45 cm and paired row planting (G2) of bhindi at 45/75 x45 cm. In normal row planting technique, one row of cowpea was intercropped in between one row of bhindi and in paired planting technique two rows of cowpea were intercropped in between pairs of rows of bhindi. Three levels of nitrogen were other treatments. The nitrogen levels tried were 100% dose of nitrogen (N1), 75% dose of nitrogen (N2) and 50% dose of nitrogen (N3). Full dose of phosphorus and potassium were applied uniformly in all these plots. In addition to these treatments, sole crop of bhindi and cowpea were raised as control plots. The results revealed that planting pattern significantly influenced most of the growth and yield contributing characters and field of bhindi. Growth characters like plant height, canopy spread, root length, total dry matter production and CGR and yield contributing characters like days to 50 per cent flowering, number of fruits per plant, fruit weight per plant, total yield of fruits and bhusa yield of bhindi were significantly higher in normal planting pattern than in paired planting pattern. The bhusa yield and pod yield of cowpea were also significantly influenced by planting pattern recording the higher value for paired row technique. The crop arrangements also influenced the nitrogen, phosphorus and potassium uptake of bhindi and cowpea. Nutrient uptake of bhindi was maximum under normal planting pattern, whereas that of cowpea was maximum under paired planting pattern. The biological indices like land equivalent ratio, area x time equivalent ratio, aggressivity and economic indices like gross return, net return, benefit/cost ratio return per rupee invested on labour and fertilizer were maximum under normal planting pattern thought the effect was not significant. The soil nutrient status was maximum under paired planting pattern. Application of nitrogen could not appreciably influence most of the growth and yield contributing characters and yield of bhindi. Nitrogen level significantly influenced canopy spread and root length and bhusa yield. Maximum growth and yield of bhindi were recorded under 75% nitrogen recommendation. Nitrogen levels had no significant influence on growth and yield of cowpea. However, maximum growth and yield of cowpea were recorded under 100% nitrogen level. The nutrient uptake by bhindi and cowpea was not influenced by nitrogen level. Land equivalent ratio and area x time equivalent ratio and land equivalent coefficient were not significantly influenced by nitrogen levels. The economic parameters revealed that 75% nitrogen dose to the intercropping system was the best. The available nitrogen, phosphorus and potassium content in the soil after the experiment were not influenced by nitrogen levels. As pure crops, bhindi and cowpea recorded maximum growth and yield contributing characters and yield as compared to the intercropping treatments. However, the economic analysis revealed that intercropping of bhindi with cowpea is advantageous than their respective sole crops. Raising a summer crop resulted in a saving of 25% nitrogen for the succeeding rice crop. The different treatments of summer cropping did not cause any variation in the yield of rice.